2016
DOI: 10.1002/cncr.30482
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐institutional analysis of peritransplantation radiotherapy in patients with relapsed/refractory Hodgkin lymphoma undergoing autologous stem cell transplantation

Abstract: BACKGROUND No consensus exists regarding the use of radiotherapy (RT) in conjunction with high-dose chemotherapy and autologous stem cell transplantation (HDC/ASCT) for patients with relapsed/refractory classical Hodgkin lymphoma (HL). The objectives of the current study were to characterize practice patterns and assess the efficacy and toxicity of RT at 2 major transplantation centers. METHODS Eligible patients underwent HDC/ASCT from 2006 through 2015 using the combination of either carmustine (BCNU), etop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
1
10
1
2
Order By: Relevance
“…These data suggest that the survival benefit observed with post‐ASCT radiotherapy in our population is unrelated to prior radiation therapy or disease burden at initial diagnosis. Milgrom and colleagues recently described practice patterns pertaining to radiation therapy in those undergoing ASCT for RR‐HL and found that patients treated with radiation therapy in the peritransplant setting were more likely to have early stage disease both at initial diagnosis and upon relapse, although radiation therapy was not associated with improved PFS or OS in that study . One explanation for improved survival in patients treated with post‐ASCT radiotherapy in the current study is the presence of more localized disease upon relapse, though this association was not explored specifically in the present study.…”
Section: Discussionmentioning
confidence: 51%
“…These data suggest that the survival benefit observed with post‐ASCT radiotherapy in our population is unrelated to prior radiation therapy or disease burden at initial diagnosis. Milgrom and colleagues recently described practice patterns pertaining to radiation therapy in those undergoing ASCT for RR‐HL and found that patients treated with radiation therapy in the peritransplant setting were more likely to have early stage disease both at initial diagnosis and upon relapse, although radiation therapy was not associated with improved PFS or OS in that study . One explanation for improved survival in patients treated with post‐ASCT radiotherapy in the current study is the presence of more localized disease upon relapse, though this association was not explored specifically in the present study.…”
Section: Discussionmentioning
confidence: 51%
“…With no prospective studies to date to guide the application of peri-transplant RT and mixed results in retrospective studies, the role of peri-transplant RT has remained controversial. [10][11][12] An older study from the mid-1990s, when RT was part of the standard upfront therapy (55% of included patients received upfront RT as part of combined modality therapy), highlighted the increased risk of relapse in sites of previous involvement, which was abrogated by the addition of peri-transplant RT. 13 In addition, more recent multi-institutional data have shown that the omission of RT as part of upfront therapy was associated with decreased salvage rates with ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…Ezekben a csoportokban a négyéves lokális kontroll 81% volt az RT-ben részesülő betegekben, szemben azokkal, akik nem kaptak RT-t (49%, p = 0,03). Ez alapján a relapsus szempontjából nagy rizikójú betegeknél alkalmazása előnyösnek tűnik [23].…”
Section: Korai Peritranszplantációs Sugárkezelésunclassified
“…Az RT dózisát vizsgálva felmerült, hogy a kemorefrakter betegeknek ≥35 Gy RT alkalmazása szükséges lehet [23,24]. Az RT alkalmazása döntően az AHSCT után javasolt, hiszen előtte alkalmazva a betegség a nem besugarazott területeken progrediálhat, illetve a csontvelő károsításával az aplasia idejét nyújthatja [23].…”
Section: Korai Peritranszplantációs Sugárkezelésunclassified